Pervaporation Of Aqueous Ethanol Solution By Carbon Nanotube-Infused Polyvinyl Alcohol Membrane Supported By Polyvinylidene Fluoride - Hashim, Nurkhairil Azhar (Universiti Sains Malaysia, 2017)
In this project, composite membranes containing non-woven cloth and polyvinylidene fluoride (PVDF) as support layer, and poly(vinyl alcohol) (PVA) incorporated with carbon nanotubes (CNT) as a selective layer were prepared for dehydration of ethanol/water mixtures by the pervaporation process. The PVA-CNT layer was fabricated via solution casting technique and the PVDF support layer was fabricated through phase inversion method. The scanning electron microscopy (SEM) results showed that the CNT fillers were dispersed in the PVA polymer matrix. The degree of swelling results showed that the CNT with the hydroxyl (–OH) and carboxyl (–COOH) functional groups in the PVA layer help to increase the degree of swelling of the membranes. The mechanical test results showed that the membrane with the PVA incorporated with CNT exhibited the highest tensile strength of11.6 MPa and strain 25.9 %. The pervaporation results showed that membranes incorporated with CNT have higher total flux, separation factor and pervaporation separation index (PSI) which were 8, 7 and 54 times, respectively.